A novel cuproptosis-related molecular pattern and its tumor microenvironment characterization in colorectal cancer - Zhu, Zhonglin; Zhao, Qiuyan; Song, Wang; Weng, Junyong; Li, Shanbao; Guo, Tianan; Zhu, Congcong; Xu, Ye (Frontiers in Immunology, 2022)
Termed as cuproptosis, copper-induced cell death has been reported as a novel noncanonical form of cell death in recent. However, the potential roles of cuproptosis in the alteration of tumor clinicopathological features and the formation of tumor microenvironment (TME) remain unclear. In this study, we comprehensively analyzed the cuproptosis-related molecular patterns of 1274 colorectal cancer samples based on 16 cuproptosis regulators. The consensus clustering algorithm was conducted to identify cuproptosis-related molecular patterns and gene signatures. The ssGSEA and ESTIMATE algorithms were used to evaluate the enrichment levels of the infiltrated immune cells and tumor immune scores, respectively. The cuproptosis score was established to assess cuproptosis patterns of individuals with principal component analysis algorithms based on the expression of cuproptosis-related genes. Three distinct cuproptosis patterns were confirmed and demonstrated to be associated with distinguishable biological processes and clinical prognosis. Interestingly, the three cuproptosis patterns were revealed to be consistent with three immune infiltration characterization: immune-desert, immune-inflamed and immune-excluded. Enhanced survival, activation of immune and high tumor purity presented in patients with low cuproptosisScore, implicating the immune-inflamed phenotype. In addition, low score was linked to high tumor mutation burden, MSI-H and high CTLA4 expression, showing higher immune cell proportion score (IPS). Taken together, our study revealed a novel cuproptosis-related molecular pattern associated with TME phenotype. The formation of cuproptosisScore will further strengthen our understanding of TME feature and instruct more personalized immunotherapy schedule in colorectal cancer.